María Celia Vázquez. Victoria Ocampo, cronista Outsider. Rosario/Buenos Aires: Beatriz Viterbo Editora. Fundación Sur, 2018, 263 pp. - Nuñez, Julieta (Badebec, 2020)
María Celia Vázquez. Victoria Ocampo, cronista Outsider. Rosario/Buenos Aires: Beatriz Viterbo Editora. Fundación Sur, 2018, 263 pp.